China and Climate Change Governance: A Golden Opportunity - Barry Buzan (China Quarterly of International Strategic Studies, 2021)
Climate change is a threat to all of humankind, yet there is still a leadership vacuum on climate governance. At the same time, the deepening climate crisis also presents a golden opportunity for Beijing to assume the role of a global leader. China has the capacity to do it in a way that the United States, Russia, India, and the European Union do not. Taking swift climate action is in Beijing’s interest. Greater contributions to climate governance will certainly help advance China’s long-term political interest in both raising its political status and demonstrating the claimed superiority of its system of government. Positive rhetoric and robust action by China are likely to have a disproportionate effect on the rest of the world. Policy adjustment and implementation by Beijing will bring benefits to the rest of the world. Climate policy options that Beijing may take in the future are not mutually exclusive. The policy shift on climate change could also be attached more firmly to the idea of sustainable development as a defining factor of China’s approach to tackling the climate change threat.